ANALISIS SWOT PADA UKM MINUMAN SARI BUAH KUNYIT ASAM DI DESA PALAAN KECAMATAN NGAJUM KABUPATEN MALANG - Wibawati, Diva Aulia Putri; Al Ahdi, Muhammad Hifzhul; Izzah, Nurul; Cahyani, Winda (JRCE (Journal of Research on Community Engagement), 2023)
This research was conducted based on the lack of an appropriate marketing strategy for “Fanbi Risky” fruit juice drink company, causing these companies to be underdeveloped. Therefore, it takes the right strategies to develop "Fanbi Riski" company. This research is a qualitative descriptive study that focuses on SWOT analysis to help “Fanbi Risky” fruit juice owner in increasing their company marketing. The data collection which was used in this research was observation method, interview method, and documentation studies. This research used SWOT matrix analysis, the strategy obtained is the WO strategy which is a strategy that utilizes Weakness factors as Opportunity factors. The implementation of this strategy is to take advantage of advances in technology and information for promotion so that sales increase, and provide modern equipment to increase the productivity of the company